Dukungan Keluarga Berhubungan Dengan Kepatuhan Hemodialisis pada Pasien Gagal Ginjal Kronik (GGK): Literature Review - Jumain; Parmi; Agustinus Talindong; Wahyu (Journal of Health (JoH), 2023)
Introduction: Chronic kidney failure (CKD) or end-stage renal disease is a progressive disorder of kidney function, in which the body's ability to fail to maintain metabolism and fluid and electrolyte balance causes uremia and excessive amounts of other nitrogenous waste products in the blood. The big problem that contributes to the failure of hemodialysis is the problem of client compliance in following the program. Purpose: To determine the relationship between family support and adherence to undergoing hemodialysis in CRF patients. Methods: this study was conducted using 5 searched articles from June 24 to July 29, 2022. Results: 10 relevant research articles were obtained. After analyzing the articles, it was found that there was a relationship between family support and adherence to undergoing hemodialysis in CRF patients and there are several factors that affect family support in undergoing hemodialysis therapy including age, gender, education, duration of HD, knowledge of HD, smoking habits, motivation, access to health services, the role of patient perceptions of nurse services and family support. Conclusion: There is a relationship between family support and adherence to undergoing hemodialysis in patients with chronic renal failure (CKD).